2011
DOI: 10.1136/vr.c6163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cross‐fostering on transfer of maternal immunity toMycoplasma hyopneumoniaeto piglets

Abstract: The aim of this study was to assess the effect of cross-fostering on transfer of maternal Mycoplasma hyopneumoniae-specific humoral and cell-mediated immunity (CMI) from gilts to piglets. Cross-fostering, carried out within gilt pairs, was based on the gilts' M hyopneumoniae vaccination status in accordance with the following scheme: six pairs of vaccinated gilt × non-vaccinated gilt (V × N); five pairs of non-vaccinated gilt × vaccinated gilt (N × V); and five pairs of vaccinated gilt × vaccinated gilt (V × V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 21 publications
2
36
0
3
Order By: Relevance
“…For example cross-fostering (the transfer of piglets between native and foster litters to match teat number or even weight distribution) may be a more challenging activity for males rather than females, as transfer from the native litter to a foster litter requires appropriate behaviours to acquire and maintain a new teat. In addition if males are likely to be more immune-compromised than females, as suggested in this study, untimely removal from the native mother's colostrum and milk supply, containing valuable immunoglobulins as well as dam specific lymphocytes to facilitate cell mediated immunity [64], [65], could be more detrimental for males than females.…”
Section: Discussionmentioning
confidence: 81%
“…For example cross-fostering (the transfer of piglets between native and foster litters to match teat number or even weight distribution) may be a more challenging activity for males rather than females, as transfer from the native litter to a foster litter requires appropriate behaviours to acquire and maintain a new teat. In addition if males are likely to be more immune-compromised than females, as suggested in this study, untimely removal from the native mother's colostrum and milk supply, containing valuable immunoglobulins as well as dam specific lymphocytes to facilitate cell mediated immunity [64], [65], could be more detrimental for males than females.…”
Section: Discussionmentioning
confidence: 81%
“…32 Although research has not evaluated the degree of difference in responses induced by colostral leukocytes from a calf's own dam versus colostral leukocytes from another cow, cross-fostering experiments in piglets suggest that effects of colostral leukocytes on neonatal cell-mediated immunity are greatest when the colostrum contains leukocytes from the neonate's dam. 33 Although multiple studies have confirmed that colostral leukocytes modify immune responses in calves in ways that seem relevant to protective immunity, to date research has not clearly shown an unequivocally beneficial effect of colostral leukocytes on practical outcomes such as calf respiratory or enteric morbidity, or induction of specific and measurable protective immunity following vaccination. Colostral leukocytes fed alone are not sufficient to protect calves from fatal disease in the neonatal period, 34 and recent studies comparing proportions of calves affected by naturally occurring diarrhea or respiratory disease after calves consume fresh maternal colostrum containing leukocytes, or frozen colostrum from their own dam 31 or other cows, 35 have shown small or variable differences in disease between the groups.…”
Section: Maternal Leukocytesmentioning
confidence: 99%
“…The higher immunoglobulin absorption takes place until 12 h after the farrowing and a loss in gut permeability occurs 24 and 36 h afterwards (Lecce et al, 1961;Lanza et al, 1995). Cross-fostering should be performed between 12 and 24 h after farrowing, before teat order has been established, so piglets could absorb the maximum of colostrum immunoglobulins and lymphocytes from their genetic dams (Bandrick et al, , 2011Pieters et al, 2008;Robert and Martineau, 2001;Straw et al, 1998).…”
Section: Introductionmentioning
confidence: 98%